The Contribution of the Wife's Role in Preaching: A Semiotic Analysis of the Film Buya Hamka - Amri, Yasirul; Mukti, Dixy Nugroho (Institut Agama Islam Yasni Bungo, 2025)
The wife's role is significant in supporting the preaching of scholars, but is often marginalized in historical narratives. Whereas Fajar Bustomi's Buya Hamka Vol.1 displays a visual representation of the wife's role in supporting and expanding the husband's da'wah. This study aims to analyze the representation of the wife's role in the film using the Roland Barthes semiotic approach, using a descriptive qualitative method with a focus on visual and narrative signs that illustrate the wife's contribution in supporting, strengthening, and expanding the husband's da'wah. The results of this study show that the wife's role is not only as an emotional supporter, but also presents the wife as a strategic partner in da'wah, actively involved in decision-making, and participation in da'wah activities. This representation provides a new understanding of the role of women in the realm of da'wah and their contribution to the spread of Islamic values, and the gender role of women in the context of Minangkabau culture that upholds the value of family honor. This film is not only an art form, but also an educational tool to strengthen awareness of the importance of women's role in the religious sphere.